2016
DOI: 10.1503/cjs.002916
|View full text |Cite
|
Sign up to set email alerts
|

Trends in revision hip and knee arthroplasty observations after implementation of a regional joint replacement registry

Abstract: Background: National joint replacement registries outside North America have been effective in reducing revision risk. However, there is little information on the role of smaller regional registries similar to those found in Canada or the United States. We sought to understand trends in total hip (THA) and knee (TKA) arthroplasty revision patterns after implementation of a regional registry. Methods:We reviewed our regional joint replacement registry containing all 30 252 cases of primary and revision THA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…27 Alternatively, Singh et al assessed Canadian data and found that the prevalence of PJI-related revision TKA remained stable over the study period. 26 In our study, PJI prevalence particularly increased in medium-and large-sized hospitals, while decreasing in small-sized hospitals. This is in line with a previous study where Bozic et al reported a consistent finding that revision TKAs were most commonly performed in large hospitals (61.3%), while only 13.7% of revision TKAs were reported in small hospitals.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…27 Alternatively, Singh et al assessed Canadian data and found that the prevalence of PJI-related revision TKA remained stable over the study period. 26 In our study, PJI prevalence particularly increased in medium-and large-sized hospitals, while decreasing in small-sized hospitals. This is in line with a previous study where Bozic et al reported a consistent finding that revision TKAs were most commonly performed in large hospitals (61.3%), while only 13.7% of revision TKAs were reported in small hospitals.…”
Section: Discussionmentioning
confidence: 42%
“…25 Singh et al reported the findings from the Canadian Joint Registry and found the prevalence of PJI-related revision TKA to be 39%. 26 The wide range in these prevalences indicates the difficulty in comparing these data among different health systems. Moreover, these differences also emphasize the need for more granular data analysis on the plethora of total knee replacements performed in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Balancing of a TKA is essential to the proper function and overall longevity of the implant. 8,17 Defining instability of the patellofemoral joint is difficult to quantify. A study by Sasaki et al assessed the influence of patella height on soft tissue balance in PS TKA and found that at 90°and 135°of flexion the joint component gap correlated with high-positioned patellae as compared with low-positioned patellae.…”
Section: Discussionmentioning
confidence: 99%
“…8,[10][11][12][13] Diminished outcomes have been associated with poorly balanced or placed patella implants and continue to be a common cause of revision TKA as evidenced in a recent study using a Canadian joint registry in which 7% of revisions were due to patella maltracking or instability. [14][15][16][17] The effect of different techniques to achieve flexionextension balance and the use of PS versus CR implant designs on patellofemoral balancing has not been previously studied. The purpose of this study is to utilize a previously validated computational analysis software (LifeMOD/Knee-SIM; LifeModeler, Inc., San Clemente, CA) to simulate the effects of patellofemoral pressure based on component position and size of femoral component in PS and CR TKA designs.…”
mentioning
confidence: 99%
“…21 The United States hopes to replicate the reduction in revision arthroplasty rates through registries seen in several other countries. 22,23 Along with AJRR, NIS relies on ICD coding to identify procedures, capture diagnoses, and report comorbidities. Errors and discrepancies in administrative databases are well documented.…”
Section: Discussionmentioning
confidence: 99%